Septic Pulmonary Embolism Secondary to Klebsiella Pneumonia Perianal Abscesses: A Case Report - Alrasheedi Sami Meateq (Wolters Kluwer Medknow Publications, 2024)
Septic pulmonary embolism (SPE) represents the occurrence of septic thrombi in circulation, originating from an extrapulmonary infectious source. Perianal and perirectal abscesses are frequently encountered anorectal issues, often stemming from obstructed anal crypt glands, resulting in pus accumulation within the subcutaneous tissue and intersphincteric plane. Timely surgical drainage is essential upon diagnosis of anorectal abscesses. Adult males exhibit a twofold higher incidence of anorectal abscesses and fistulae compared to females, with common symptoms including excruciating anal or rectal pain. This case report details the presentation and management of a 42-year-old male patient afflicted by Klebsiella pneumonia perianal abscesses that led to SPE. The report underscores the importance of recognizing and treating anorectal abscesses promptly to avert potentially life-threatening complications such as sepsis and fistulae.